Luteolin ameliorates palmitate-induced lipotoxicity in hepatocytes by mediating endoplasmic reticulum stress and autophagy. (January 2023) - Huang, Chun-Yin; Chen, Haw-Wen; Lo, Chia-Wen; Wang, Yu-Ru; Li, Chien-Chun; Liu, Kai-Li; Lii, Chong-Kuei
Abstract: Abnormal accumulation of lipids in liver leads to uncontrolled endoplasmic reticulum (ER) stress and autophagy. Luteolin is known to have antioxidant, anti-inflammatory, and anti-cancer properties, but whether it protects against lipotoxicity in liver remains unclear. In this study, we challenged AML12 liver cells and mouse primary hepatocytes with palmitic acid (PA) with or without luteolin pretreatment. In the presence of PA, reactive oxygen species (ROS) production was increased at 3 h, followed by enhancement of expression of p-PERK, ATF4, p-eIF2α, CHOP, and TXNIP (ER stress markers) and p-p62 and LC3II/LC3I ratio (autophagy markers), in both primary hepatocytes and AML12 cells. When PA treatment was extended up to 24 h, apoptosis was induced as evidenced by an increase in caspase-3 activation. RFP-GFP-LC3B transfection further revealed that the fusion of autophagosomes with lysosomes was damaged by PA. With luteolin treatment, the expression of antioxidant enzymes, i.e., heme oxygenase-1 and glutathione peroxidase, was upregulated, and PA-induced ROS production, ER stress, and cell death were dose-dependently ameliorated. Luteolin could also reverse the damage caused to autophagic flux. These results indicate that luteolin protects hepatocytes against PA assault by enhancing antioxidant defense, which can attenuate ER stress and autophagy as well as promote autophagic flux. Highlights: Palmitic acid induces ER stress by activating PERK-dependent pathway. Palmitic acid enhances autophagy and damages autophagic flux. Luteolin protects against palmitic acid-induced ER stress, autophagy, and apoptosis. Luteolin promotes antioxidant defense in hepatocytes.